2017
DOI: 10.4081/aiua.2017.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Premature ejaculation: Pharmacotherapy vs group psychotherapy alone or in combination

Abstract: Objectives: Premature Ejaculation (PE), the commonest sexual dysfunction in males, is generally treated with local anesthetic and SSRI (Dapoxetine). The aim of our study was investigate Group Psychotherapy as an alternative treatment for PE and compare the efficacy of pharmacological treatment and psychotherapy, either alone or in combination, in terms of response and improved Quality of Life (QoL). From a male outpatient population screened for PE, those who received a diagnosis of PE were proposed for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…After removing 1736 papers through the title/abstract screening, 91 were retrieved as full text. Of the 91 full text, 36 studies were excluded because they were theoretical, opinion, focused on erectile dysfunction or included only pharmacological treatments, leaving 54 studies to be included in the systematic review 14–67 …”
Section: Resultsmentioning
confidence: 99%
“…After removing 1736 papers through the title/abstract screening, 91 were retrieved as full text. Of the 91 full text, 36 studies were excluded because they were theoretical, opinion, focused on erectile dysfunction or included only pharmacological treatments, leaving 54 studies to be included in the systematic review 14–67 …”
Section: Resultsmentioning
confidence: 99%
“…Considering all these negative effects, behavioral treatments and pelvic floor training to alleviate premature ejaculation are of great importance. Although there are many studies [ 16 , 19 , 23 ] examining the effects of behavioral therapy and pelvic floor exercises on men with premature ejaculation in the literature, no study has been found comparing the stop-start technique with the stop-start technique together with sphincter control training. This study is expected to contribute to the literature by investigating the stop-start technique, which is a current approach in the treatment of premature ejaculation, and comparing its results with the stop-start technique together with sphincter control training.…”
Section: Discussionmentioning
confidence: 99%
“…When we look at the studies in the literature, we see the studies on the effect of the stop-start technique on the PEDT value. For example, in the study of Pavone et al (2017), it was observed that the PEDT value decreased after the application [ 16 ]. In Mantovani’s (2017) study on 18 patients, it was found that the PEDT value decreased in the post-test compared to the pre-test [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual male dysfunction is an extremely common condition that manifests itself with erectile disorder (ED) and premature ejaculation (EP) (1), often present at the same time. In everyday clinical practice, both pathologies require a multidisciplinary approach in the diagnostic phase and in the therapeutic management (2,3) due to their multifactorial genesis, such as psychological factors and endothelial dysfunction. Female sexual dysfunctions are understudied, despite the incidence being alarmingly high: in a 30 years ago study, 76% of women were living with some symptoms of sexual dysfunction (4), while more recent literature suggest that prevalence is around 43% (5).…”
Section: Introductionmentioning
confidence: 99%